Transições de fase em modelos magnéticos bi-dimensionais com interações dipolares. - Lucas Alvares da Silva Mol (2009)
In this work we have used the numerical Monte Carlo simulations to simulate the planar to paramagnetic phase transition in the anisotropic Heisenberg model with dipolar interactions (AH-d model). We concentrated our attention in three slightly different models the AH-d model in a bilayer system with a cut-off in the dipolar interactions, the dipolar Planar Rotator model (d-PR) and the HA-d model in a square lattice, using the Ewald summation to evaluate the dipolar interactions. Our results indicate that these models belong to a new universality classwith long range order in the low temperature phase and a non-divergent specific heat.